Border problems: Mapping the third border - ALLEN, Jason Grant (Institutional Knowledge at Singapore Management University, 2020)
The Internet has become the site of economically relevant objects, events and actions, as well as the source of potential risks to the financial systems. This article builds on a metaphor of ‘border problems’ in financial regulation, exploring a ‘third border’ between the ‘real world’ and ‘cyberspace’—a virtual domain of human interaction facilitated and conditioned by digital communications systems. Reviewing the ‘cyber-sovereignty’ debate and surveying the divergent approaches now emerging along geo-political faultlines, we argue that sovereign states still have a unique and irreplaceable role in guarding financial stability which must be reflected in the law of Internet jurisdiction: an emerging lex cryptographica financiera. We conclude with a few observations on how this could affect the design of financial regulation in the coming decade.